An Optimasi Lube Oil Cooler Fan Saat Unit Pembangkit Listrik Tenaga Gas Dan Uap Priok Reverse Shutdown - Raihan Muhammad Raihan (Sekolah Tinggi Teknik PLN, 2023)
Lube oil cooler fan at Combine Cycle Power Plant (CCPP) Block 1-2 PT. PLN Indonesia Power Priok is used as a heat exchanger to reduce the temperature of the lubricant that has passed through the system so that it can return through the system at a lower temperature. CCPP Block 1-2 often experience Start-Shutdown units due to requests from the PLN load regulator, therefore the lube oil cooler fan often continues to operate even though the lubricant temperature is low during the Shutdown (RS). The lube oil cooler fan optimization program is an activity to turn off one fan during the reverse shutdown unit and turn off all the fans manually by the operator when the lubricant temperature is below 42oC and then recorded for documentation. This activity is contained in the Standard Operating Procedure regarding energy saving during RS Gas Turbines. With the existence of an optimization program for operating patterns by turning off the lube oil cooler fan, it is hoped that it will be able to reduce power, with the target of reducing electric power consumption by 40,000 KWh per year. This program can save 165,454.34 kWh of power in 2020, or the equivalent of 595.64 GJ, and in 2021 it can save 101,468.40 kWh of energy, or the equivalent of 365.29 GJ.